Impaired Discriminative Function in Patients with Chronic Pain Measured by Variance in Straight Leg Raising - Ann Marie Hoirch; Vicky Smith; Sophie Beugnot; Joanne Turner; Richard FH Catchlove (Pain Research and Management)
Many chronic pain patients seem to have difficulty regulating exercise programs and require detailed, precise instructions of what exercises to do as well as their frequency and timing. This may be due to a lack of information concerning the state of the damaged tissues, which may result from inadequate feedback mechanisms for pain, stretch and position. The straight leg raising test was used as a model of this mechanism, and variance in targeting the end-point of this test was measured in patients with chronic pain and in controls. Variance about the end-point in chronic pain patients was more than three times larger than that in controls. Although chronic pain patients were older, there was no correlation between straight leg raising and age. The implications of these findings to the maintenance of the original injury and the importance of this in the maintenance and continuation of chronic pain states are discussed.